Recent Advances and Future Prospects of Lithium Recovery from Low-Grade Lithium Resources: A Review - Jihan Gu; Binjun Liang; Xianping Luo; Xin Zhang; Weiquan Yuan; Bin Xiao; Xuekun Tang (Inorganics)
The growing demand for lithium, driven by the widespread adoption of electric vehicles and renewable energy storage systems, has sparked interest in developing low-grade lithium resources. This comprehensive review explores the types, distribution, extraction technologies, challenges, and future prospects of low-grade lithium resources. This article focuses on low-grade lithium sources such as clays, brines, coal, and coal by-products, and analyzes the principles, advantages, and limitations of key extraction techniques, including acid-alkaline leaching, bioleaching, adsorption, and membrane separation. Furthermore, this review discusses the technical, economic, and environmental sustainability challenges associated with developing low-grade lithium resources and proposes corresponding strategies. Future research should focus on improving the selectivity and efficiency of extraction and processing technologies, optimizing separation processes, and developing green and cost-effective extraction methods. Establishing supportive policy frameworks, strengthening international cooperation, and knowledge sharing are crucial for promoting the sustainable development of low-grade lithium resources. This review provides stakeholders with comprehensive insights and recommendations for addressing the growing lithium demand and achieving the Sustainable Development Goals.